MENINGKATKAN KETERAMPILAN MEMBUAT PALAI RINUAK MELALUI METODE LATIHAN PADA ANAK TUNAGRAHITA RINGAN - Eli Haryeti, Asep Ahmad Sopandi, Mega Iswari (Jurnal Penelitian Pendidikan Khusus, 2013)
This research aim to: demonstrate the effectiveness of training methods in improving the skills of making palai rinuak for mild mental retardation children in the DV classes at State SDLB 64 Surabayo Lubuk Basung. This research use approach of Single Subject Reaserch (SSR) with A-B desain. Research subjects are children mild mental retardation "X". Target size of their behavior is "percentage" children's ability to make palai rinuak, from the steps of the 15 steps. Data was collected through the registration procedure with direct observation by researchers and test. Recording in a format of data collection that has been provided. The data obtained were processed in the graph. Results showed that children's skills in making palai rinuak increased after given learning training methods. This is evident in the baseline phase (A) before the intervention given the child's ability to master only (5) steps (33.3%) making skills palai rinuak properly. Once the child is given the intervention (B) by using the method of practice learning keampuan child has a maximum, meaning that the child is able to do all the steps (100%) of the predefined 15langkah in palai rinuak making skills properly. It can be concluded that an effective training method to improve the skills of making palai rinuak. Thus it is advisable for teachers and further research in order to use training methods to improve other skills.